Street dance redefined: a bridge across the knowledge gap - Xi Ling (Frontiers in Sports and Active Living)
IntroductionStreet dance research has expanded rapidly since its inception, yet the absence of a unified terminology has produced inconsistent academic interpretations and a substantial knowledge gap. This study aimed to establish a clear definition of “street dance,” classify its common styles, and identify the factors underlying terminological inconsistency.MethodsFollowing PRISMA guidelines, we conducted a systematic review. Indicative Behavioral Standards were applied to critically appraise 26 peer-reviewed articles retrieved from major databases. Data extraction focused on terminological usage, style descriptions, and reported sources of conceptual divergence.ResultsThe review revealed wide variability in definitions and style classifications across the literature. Synthesizing these findings, we reconstructed a concise, consensus-based definition of street dance and proposed a classification framework for common street dance styles. This review identified internal and external factors contributing to the knowledge gap. Internal factors including individual creativity, knowledge transmission. External factors including national cultural, media communication, music development, public opinion.DiscussionThe reconstructed definition and classification system standardize street dance terminology, offering researchers, educators, and practitioners a coherent conceptual framework. This advancement enhances scholarly communication and supports more rigorous future investigations within the global street dance community.